Influence of Tiktok Account @dokterdetektif Credibility on Followers Trust in Information - Hamzah, Adrian Fadhullah; Destiwati, Rita (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The credibility of anonymous influencer accounts is a critical, yet unexplored factor in building audience trust in health information on social media, especially on platforms like TikTok. This study examines the influence of the credibility of the anonymous account @dokterdetektif (2.1 million followers) on the trust of its followers. Quantitative research was conducted through an online survey of 400 active followers (purposive sampling, Slovin formula, 5% margin of error). The 4-point Likert scale questionnaire measured three dimensions of credibility (attractiveness, expertise, trustworthiness) and two dimensions of trust (trusting belief, trusting intentions). Validity was tested using Pearson correlation, reliability using Cronbach's Alpha (α>0.7), and hypothesis testing using Spearman correlation and t-test. There was a significant correlation between account credibility and audience trust (r=0.576; p<0.05), with credibility explaining 43.4% of the variance in trust (R²=0.434). All three dimensions of credibility were rated "very high": attractiveness (mean 3.62), expertise (3.58), and trustworthiness (3.54). These findings are in line with the audience trust dimension, proving that perceived credibility is the main foundation of information trust. Influencers need to build multidimensional credibility to increase trust, while audiences must critically evaluate information. Future research is suggested to explore non-credibility factors (e.g. algorithm bias) and use qualitative approaches to understand audience motivations in depth.